In-hospital outcomes of patients undergoing concomitant aortic and mitral valve replacement in Germany. (15th December 2021) - Kreibich, Maximilian; Kaier, Klaus; von zur Mühlen, Constantin; Siepe, Matthias; Zehender, Manfred; Bode, Christoph; Beyersdorf, Friedhelm; Stachon, Peter; Bothe, Wolfgang
Abstract:  : OBJECTIVES: To evaluate in-hospital outcomes of concomitant mitral valve replacement (MVR) in patients undergoing conventional aortic valve replacement due to aortic stenosis in a nationwide cohort. METHODS: Administrative data from all patients with aortic stenosis undergoing conventional aortic and concomitant MVR (reason for MVR not specified) between 2017 and 2018 in Germany were analysed. RESULTS: A total of 2597 patients with a preoperative logistic EuroScore of 9.81 (standard deviation: 8.56) were identified. In-hospital mortality was 6.8%. An in-hospital stroke occurred in 3.4%, acute kidney injury in 16.3%, prolonged mechanical ventilation of more than 48 h in 16.3%, postoperative delirium in 15.8% and postoperative pacemaker implantation in 7.6% of the patients. Mean hospital stay was 16.5 (standard deviation: 12.1) days. Age [odds ratio (OR): 1.03; P  = 0.019], New York Heart Association class III or IV (OR: 1.63; P  = 0.012), previous cardiac surgery (OR: 2.85, P  = 0.002), peripheral vascular disease (OR: 2.01, P  = 0.031), pulmonary hypertension (OR: 1.63, P  = 0.042) and impaired renal function (glomerular filtration rate <15, OR: 3.58, P  = 0.001; glomerular filtration rate <30, OR: 2.51, P  = 0.037) were identified as independent predictors for in-hospital mortality. CONCLUSIONS: In this nationwide analysis, concomitant aortic and MVR was associated with acceptable in-hospital mortality, morbidity and length of in-hospital stay. The regression analyses may help to identify high-risk patients and further optimize treatment strategies. Abstract : Aortic valve stenosis is the most prevalent valvular heart disease often necessitating aortic valve replacement (AVR).